Demographic and clinical analysis of post sterilization failure cases in a tertiary care hospital, Chennai, Tamil Nadu, India - Meena, T. S.; Ramya, K. S.; Mothilal, R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The most common permanent method of family planning accepted in India is female tubal sterilization as it has a very low failure rate of 0.1- 0.8% in the first year and over all pregnancy chances of 1 in 200. It can be done by open method but laparoscopic method has now gained wide popularity. Methods: Ours was a retrospective study of post female sterilization failure cases admitted to the Department of Obstetrics and Gynecology, Government Kilpauk Medical College Hospital within a 10 year time period between April 2007 and March 2017. Results: Over a decade we had 134 post sterilization failures. 71 patients presented with intrauterine pregnancy whereas 63 presented as ectopic pregnancy following sterilization. Majority of patients belonged to 26-30 year age group and the median age was 28 years. 40.3% ectopic presented at 5-6 weeks gestational age. Over 90% of sterilization failures were done by open method and around 35.8% were done during caesarean section. Around 65.0 % sterilization failures were seen within 5 years of sterilization but 2 patients presented as late as 17 years post sterilization. In four cases (3%) failure was due to improper surgical procedure. Conclusions: Female sterilization may result in failure even after years of sterilization. In the present study, pregnancy after sterilization is higher in the youngest age group (15-30) years than for the age group (31-35) years and stabilized in the oldest age group (36-49) years. Open sterilization had a higher failure rate than laparoscopic sterilization. The most common mode of sterilization failure was intrauterine pregnancy than the ectopic pregnancy and it was almost equal to each other. Therefore, patients undergoing sterilization must be counselled about chances of failure; even though it is a permanent method, and to consult immediately if missed period else at a later stage they may go in for rupture ectopic leading to high maternal morbidity and mortality.